Synthesis, Characterization And Antimicrobial Activity Of Substituted Tricyclic Compounds: 5,6,7,8-Tetrahydro Pyrido[4',3':4,5]Thieno[2,3-D]Pyrimidines - MANISH MITTAL,; SURAJ M. SARODE,; DR. G. VIDYASAGAR, (International Journal of Pharma and Bio Sciences, 2011)
As a part of systematic investigation for synthesis, characterization and biological activity of several new substituted tricyclic compounds: 7-(phenylsulfonyl)-N-(phenyl)-5,6,7,8-tetrahydropyrido[4’,3’:4,5]-thieno[2,3-d]pyrimidin-4-amine (7a-7t) have been synthesized from 7-(phenylsulfonyl)-4-(chloro)-5,6,7,8-tetrahydropyrido[4’,3’:4,5]-thieno[2,3-d]pyrimidine (6a-6e) using piperidin-4-one Hydrochloride and benzenesulfonyl chloride as the starting material. All the synthesized products were evaluated for their antibacterial activity against Bacillus substilis, Escherichia coli. Klebsiella pneumoniae and Streptococcus aureus bacteria and antifungal activity against Aspergillus niger, Aspergillus flavus, Fusarium oxisporium and Trichoderma viride fungi respectively. Most of the synthesized compounds exhibited significant anti-bacterial and anti-fungal activities. The structures of all the synthesized compounds have been determined by their spectral and microanalytical data.